ANALISIS PERAN PUSKESMAS KEDUNGMUNDU KOTA SEMARANG DALAM MELAKSANAKAN PROGRAM DETEKSI DINI KANKER LEHER RAHIM DAN KANKER PAYUDARA - Loveloi Putri Sihanari; Sutopo Patria Jati; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2018)
Cervical and Breast Cancer Screening Program is the government program to overcome cervical cancer with VIA method and breast cancer with CBE method. Kedungmundu Primary Healthcare Center is the one of Primary Helatcare Center that provides inspection services of VIA and CBE. In 2017, incidences of cervical and breast cancer in Kedungmundu Primary Healthcare area are high, that is 28 cases. Meanwhile the number of women of reproductive age are screened in 2015−2017 has not reached the targets. This study aims to analyze the role of Kedungmundu Primary Healthcare Center in implementating cervical and breast cancer screening program. This research used descriptive qualitative method with purposive sampling criteria toward and deep interviews with 2 main informant and 13 triangulation informant. The result of this research shows that the role of passive and active role of primary health care center has not been done optimally. In carrying out of passive role, there are constraints that is the lack of trained IVA’s midwives and not reaching the national targets. While on the active role, socialization and education of primary health care center is not directly to the people, the reports of VIA and CBE’s performance programs has not included in the Annual Performance Report of the primary health care center. To reduce the existing obstacles, primary health care center takes advocacy and partnership to seek community participation. Monitoring and evaluation programs are not routinely performed once a month. Primary health care center strategy to increase early detection coverage is by conducting free checking in every village regularly once a month for participants who have BPJS. The health department is advised to evaluate the availability of trained midwives, targeting and improving program oversight. Primary healthcare center are advised to include VIA and CBE perfomarnce reports in the Annual Performance Report, increase partnerships, and integrate with other programs.